The Hungarian Innovational Potential and the R&D Sector - Keresztes Gábor (E-CONOM, 2012)
Usually, when one says „innovation”, novelty and the ability to renew come to mind. The measurement of the concept has become a very important field of study and a key indicator of national economies. In this article, after a short review of the theoretical approaches to innovation, I am going to examine the status of the Hungarian R&D sector. Where is Hungary now in terms of innovational activities? Who are the actors and the funders of the system, and more importantly: in what proportion? What fields are prominent in domestic practice? Amongst others, I set out to find the answers to these questions in this article. Keywords: innovation, R&D, innovational performance, financing JEL Codes: I23, O31, Q55